2022
DOI: 10.2169/internalmedicine.9308-22
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Onset of Isolated and Unilateral Abducens Nerve Palsy Associated with COVID-19 Infection: A Case Report and Literature Review

Abstract: Cranial nerve palsy associated with coronavirus disease 2019 (COVID-19) is rare. We herein report the first Asian case of the immediate onset of isolated and unilateral abducens nerve palsy (ANP) accompanied with COVID-19 infection. A 25-year-old man developed diplopia one day after the COVID-19 symptom onset. Neurological examination revealed limitation of left eye abduction without ataxia and hyporeflexia. Negative anti-ganglioside antibody results and mild albuminocytological dissociation were noted. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…More recently, several authors have reported cases of isolated abducens paralysis in patients with COVID-19 [20][21][22][23][24]. A single case involving abducens paralysis without respiratory symptoms was also described [20].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, several authors have reported cases of isolated abducens paralysis in patients with COVID-19 [20][21][22][23][24]. A single case involving abducens paralysis without respiratory symptoms was also described [20].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, several authors have reported cases of isolated abducens paralysis in patients with COVID-19 [21][22][23][24][25]. A single case involving abducens paralysis without respiratory symptoms was also described [21].…”
Section: Discussionmentioning
confidence: 99%
“…Anosmia and ageusia accompanied another case, raising the possibility of CNS invasion through the olfactory bulbs [20]. Since then, numerous additional abducens palsies have been described in association with COVID-19 [21][22][23] including one with a right abducens nucleus lesion [24] and another mimicking Wernicke's encephalopathy [25]. In a case accompanied by ipsilateral central retinal artery occlusion, Hollenhorst plaques and posterior ischemic optic neuropathy in a 68-year-old man with atrial fibrillation [26], the abducens palsy was attributed to infarction, with watershed diffusion positivity seen throughout the brain on MRI, although whether the underlying etiology was embolic or vasculitic remains unclear.…”
Section: Abducens Palsymentioning
confidence: 99%